2000
DOI: 10.1063/1.1287770
|View full text |Cite
|
Sign up to set email alerts
|

On the role of the pore filling medium in photoluminescence from photochemically etched porous silicon

Abstract: Porous silicon thin films created under laser illumination in fluoride solutions without biasing have been studied by a variety of techniques to investigate the film structure and photoluminescence (PL). The use of ultrathin silicon wafers allows us to perform plan view transmission electron microscopy studies without recourse to thinning procedures that might adversely affect the film structure. Supercritically dried samples are compared to air dried samples and clearly demonstrate the deleterious effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 49 publications
6
34
1
Order By: Relevance
“…33 We have not verified by in situ infrared absorption measurements whether an oxide layer forms during photoelectrochemical etching as employed in this study, corresponding to the electropolishing regime above the critical current density in anodic etching. However, since a por-Si layer forms, which we have confirmed by scanning electron microscopy, 34,35 photoluminescence, 35,36 profilometry, 22 and porosity measurements, 37 the reaction we observe is within the porous silicon formation regime rather than the electropolishing regime. Moreover, we have previously shown 22 that Gaussian laser intensity profiles lead to Gaussian film profiles.…”
Section: Introductionsupporting
confidence: 81%
“…33 We have not verified by in situ infrared absorption measurements whether an oxide layer forms during photoelectrochemical etching as employed in this study, corresponding to the electropolishing regime above the critical current density in anodic etching. However, since a por-Si layer forms, which we have confirmed by scanning electron microscopy, 34,35 photoluminescence, 35,36 profilometry, 22 and porosity measurements, 37 the reaction we observe is within the porous silicon formation regime rather than the electropolishing regime. Moreover, we have previously shown 22 that Gaussian laser intensity profiles lead to Gaussian film profiles.…”
Section: Introductionsupporting
confidence: 81%
“…The Bruggeman equation for oxidised porous silicon inserted polymer PMMA-DR1can be written as: The calculated index of film can be obtained according measured porosity ρ of oxidised porous silicon and the polymer fraction γ from Eq. (8). Table 1 shows that the calculated refractive index based on Bruggeman model are conform to measured results generally in our experiment.…”
Section: Methodssupporting
confidence: 86%
“…The solution was filtrated to remove foreign substance. The deposition method of immersion under ultrasonic agitation can be used to add the solution into the pore of oxidised porous silicon in our experiment 8 . Three oxidised porous silicon samples with the same porosity were prepared under different ultrasonic agitation time.…”
Section: Methodsmentioning
confidence: 99%
“…Some experimental data and theoretical investigations suggested that amorphous Si nanostructures are subjected to quantum confinement effect [6][7][8], while others showed that the short mean free path, order of 1 nm, of amorphous Si is responsible for no quantum confinement effect [2,4,9]. In addition, it was found that the quantum confinement mechanism alone cannot be used to explain the influence of various surface treatments and surrounding media on the luminescence properties [10][11][12]. Some theoretical calculations have shown that optical properties of silicon nanoparticles are highly sensitive to localized surface states, which exist in the form of self-trapped excitons and are stabilized in smaller nanoparticles due to the band gap widening [13].…”
Section: Introductionmentioning
confidence: 96%